Pharmacodynamics of Ceftibuten: An Assessment of an Oral Cephalosporin against Enterobacterales in a Neutropenic Murine Thigh Model - Maxwell J. Lasko; Tomefa E. Asempa; David P. Nicolau (MDPI AG, 2021)
Efforts to develop and pair novel oral β-lactamase inhibitors with existing β-lactam agents to treat extended spectrum β-lactamase (ESBL) and carbapenemase-producing Enterobacterales are gaining ground. Ceftibuten is an oral third-generation cephalosporin capable of achieving high urine concentrations; however, there are no robust data describing its pharmacodynamic profile. This study characterizes ceftibuten pharmacokinetics and pharmacodynamics in a neutropenic murine thigh infection model. Enterobacterales isolates expressing no known clinically-relevant enzymatic resistance (n = 7) or harboring an ESBL (n = 2) were evaluated. The ceftibuten minimum inhibitory concentrations (MICs) were 0.03-4 mg/L. Nine ceftibuten regimens, including a human-simulated regimen (HSR) equivalent to clinical ceftibuten doses of 300 mg taken orally every 8 h, were utilized to achieve various fT > MICs. A sigmoidal Emax model was fitted to fT > MIC vs. change in log10 CFU/thigh to determine the requirements for net stasis and 1-log10 CFU/thigh bacterial burden reduction. The growth of the 0 h and 24 h control groups was 5.97 ± 0.37 and 8.51 ± 0.84 log10 CFU/thigh, respectively. Ceftibuten HSR resulted in a -0.49 to -1.43 log10 CFU/thigh bacterial burden reduction at 24 h across the isolates. Stasis and 1-log10 CFU/thigh reduction were achieved with a fT > MIC of 39% and 67%, respectively. The fT > MIC targets identified can be used to guide ceftibuten dosage selection to optimize the likelihood of clinical efficacy.